Redescription of Castianeira zetes Simon, 1897 (Araneae, Corinnidae, Castianeirinae) - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2018)
The corinnid species Castianeira zetes was described by Simon in 1897. It has been redescribed several times (Gravely 1931; Tikader 1981; Tikader & Biswas 1981; Majumder & Tikader 1991; Biswas & Raychaudhuri 2000; Sen et al. 2015; Dhali et al. 2017), but none of the above works provided comprehensive somatic as well as genitalic descriptions of the species, and it still remains known only by quite poor drawings. The aim of the present paper is to redescribe and illustrate C. zetes in detail based on the type and new materials.